Apoptose no carcinoma de próstata - Fermozelli, Ricardo Abeche [UNESP] (2015)
Prostate carcinoma is a frequent cause of morbidity and mortality in Western populations, with high frequency in Brazil. It is the most common cancer among men and the second leading cause of death, preceded by lung cancer. Its incidence has increased continuously in recent decades due to increased life expectancy and the western lifestyle. Apoptosis is a cell death mechanism that occurs in many physiological processes. It is known that tumors show progressive resistance to apoptosis. It is regulated by caspases, apoptosis effector enzymes, whose activation is strictly controlled by Innibitors of Apoptosis Proteins, IAPs, which in turn are modulated by IAP activity inhibitory molecules, with SMAC/Diablo being the main one and the most studied. We studied the relationship between IAPs (XIAP and Survivin) and SMAC in prostatic carcinomas and its correlation with the Apoptotic Index (AI), cellular proliferation, immunohistochemistry expression of protein p53 and patient survival rate. TMA paraffin blocks were made with prostate cancer tissue from patients operated at the Clinics Hospital, Botucatu School of Medicine, from 1980 to 2000. These were submitted to immunohistochemical reaction to Survivin, XIAP, SMAC, p53, cleaved Caspase 3 (apoptotic index) and Ki67 (cell proliferation index). The slides were read by two pathologists, wich graduated the intensity and percentage of positive cells according to immuno-expression of each marker. These results were correlated with the Gleason grade, prognostic categories (ISUP) and patient survival data. A correlation was verified between tumor differentiation and the cell proliferation rate. The intensity of p53 reaction was also associated with the degree of neoplastic differentiation. Patient survival was higher in cases with lower ki67 labelling and lower Gleason and Prognostic Categories grading